Chapter Une métaphysique thomiste florentine. Notule sur le traité De modis rerum de Remigio de' Girolami - Imbach, Ruedi (Reti Medievali E-Book, 2020)
This article examines Remigio de' Girolami's treatise De modis rerum. This metaphysical treatise addresses all aspects of this discipline, which, in the footsteps of his master Thomas Aquinas, Remigio understands as an ontology. The investigation confirms the Thomistic orientation of Remigio's philosophy but also highlights Remigio's acute perception of the complex relationships between thought, language and reality. Thus, the author argues that this treatise proposes an innovative approach to metaphysics based on the study of the meanings of key notions of the discipline.